Genotyping-by-Sequencing Based Genetic Mapping Identified Major and Consistent Genomic Regions for Productivity and Quality Traits in Peanut - Jadhav, Mangesh P.; Gangurde, Sunil S.; Hake, Anil A.; Yadawad, Arati; Mahadevaiah, Supriya S.; Pattanashetti, Santosh K.; Gowda, M. V. Channabyre; Shirasawa, Kenta; Varshney, Rajeev K.; Pandey, Manish K.; Bhat, Ramesh S. (Frontiers in Plant Science, 2021)
With an objective of identifying the genomic regions for productivity and quality traits in peanut, a recombinant inbred line (RIL) population developed from an elite variety, TMV 2 and its EMS-derived mutant was phenotyped over six seasons, and genotyped with genotyping-by-sequencing (GBS), AhTE and SSR markers. The genetic map with 700 markers spanning 2438.1 cM was employed for quantitative trait loci (QTL) analysis which identified a total of 47 main-effect QTLs for productivity and oil quality traits with the phenotypic variance explained (PVE) of 10-52% over the seasons. A common QTL region (46.7-50.1 cM) on Ah02 was identified for the multiple traits like number of pods per plant, pod weight per plant, shelling percentage, and test weight. Similarly, a QTL (7.1-18.0 cM) on Ah16 was identified for both shelling percentage and protein content. Epistatic QTL analysis identified main-effect QTLs interacting with other genomic regions in addition to detecting several intra- and inter-chromosomal interactions for the productivity traits. The markers identified by single marker analysis mapped to the QTL regions for most of the traits. Among the five potential candidate genes identified for protein content, shelling percentage and oil quality, two genes (Arahy.7A57YA and Arahy.CH9B83) were affected by AhMITE1 transposition, and three genes (Arahy.J5SZ1I, Arahy.MZJT69 and Arahy.X7PJ8H) involved functional SNPs. With major and consistent effects, the genomic regions, candidate genes and the associated markers identified in this study would provide an opportunity for gene cloning and genomics-assisted breeding for increasing the productivity and enhancing quality of peanut.